Impacto dos investimentos socioambientais sobre a taxa de crescimento de empresas brasileiras - Ferreira, Vanessa Elionara Souza (2016)
The attention focused on actions involving social responsibility by companies has been an increasingly common theme in literature. The current economic climate has required of organizations a more ethical and focused on social and environmental issues approach, going beyond traditional financial matters. More than a social function of organizations, social and environmental investments now represent a competitive strategy. Several studies have examined the impact of such investments on the economic performance of organizations, but there is no consensus about its importance and level of relationship. In this sense, the present study aims to investigate the relationship between social and environmental investments and the economic growth rate of Brazilian companies. For that, was collected on a database called “Balanço Social” economic data from a sample of 130 companies, with publications over the period between 2000 and 2008, and based on the data panel and with the help of a statistical tool was estimated a regression model seeking the visualization of the ratio between the environmental investments and economic performance metrics, such as the rate of operational and net results of the firm. Although the relationship between the external social investments and the applied growth rates has been to a pattern of the U-shaped curve, the internal social and environmental investments showed, as expected, a pattern of an inverse U-shaped curve, as presented by Kuznets (1955), based in which it was possible to verify the level of investment that maximizes the performance of the firm. Through the knowledge of such values can be identified which companies operate at levels below the 'optimal level', suggesting the growth rate required to reach the equilibrium levels